Effect of gibberellic acid on photosynthesis and oxidative stress response in maize under weak light conditions - Fu, Jianjun; Li, Linlin; Wang, Shuang; Yu, Na; Shan, Hong; Shi, Zhensheng; Li, Fenghai; Zhong, Xuemei (Frontiers in Plant Science, 2023)
Gibberellin (GA) is an important endogenous hormone involved in plant responses to abiotic stresses. We used a pair of near-isogenic inbred maize lines comprising, SN98A (light-sensitive inbred line) and SN98B (light-insensitive inbred line) to study the effects of exogenous gibberellin A3 (GA3) application on different light-sensitive inbred lines under weak light conditions. After shade treatment, the photosynthetic physiological indexes and antioxidant enzyme activities were always lower in SN98A than those in SN98A. GA3 treatments significantly reduced the barren stalk ratios in SN98A and improved its seed setting rates by increasing the net photosynthetic rate (Pn), transpiration rate (Tr), stomatal conductance (Gs), photosynthetic pigment contents, photochemical efficiency of photosystem Ⅱ (PS II) (Fv/Fm), photochemical quenching coefficient (qP), effective quantum yield of PSII photochemistry (ΦPSII), and antioxidant enzyme activities, where the most effective treatment was 60 mg L–1GA3. GA3 treatment also regulated the metabolism of reactive oxygen species (ROS) and reduced the superoxide anion (O2-) production rate, H2O2 content, and malondialdehyde content. Compared with the control, GA3 treatment significantly increased the expression levels of APX and GR in SN98A, and APX, Fe-SOD, and GR in SN98B. Weak light stress accelerated leaf senescence, and exogenous GA3 application inhibited the ROS levels in the leaves and maintained normal physiological functions in the leaves. These results demonstrate that photosynthesis, ROS metabolism and protective mechanisms, and the expression of key genes play critical roles in enhancing the adaptability of plants to weak light stress.